The impact of generative AI on academic reading and writing: a synthesis of recent evidence (2023–2025) - Sanz-Tejeda, Aránzazu; Domínguez-Oller, Juana Celia; Baldaquí-Escandell, Josep María; Gómez-Díaz, Raquel; García-Rodríguez, Araceli (Frontiers in Education, 2026)
IntroductionThe aim of this systematic review is to examine the scientific literature published on digital reading and writing in higher education within the field of social sciences, assisted by generative artificial intelligence.MethodsThe PRISMA methodology and the SALSA Framework were applied, based on a bibliographic search conducted in the Scopus and Web of Science databases. Journal articles that explicitly addressed the established topic, published between 1 January 2023 and 7 March 2025, in open access, in Spanish or English, and within the field of Social Sciences, were included. After a rigorous screening and selection process, a final sample of 136 articles was compiled and used as the basis for the study.ResultsThe findings indicate that the reviewed research employs a range of methodologies, encompassing quantitative (surveys, experimental studies, psychometric evaluations), qualitative (case studies, semi-structured interviews, thematic analysis), and mixed-method approaches. The results also reveal a clear trend toward the integration of artificial intelligence tools –particularly ChatGPT– into academic writing processes. A significant improvement is observed in the quality of students’ texts, especially regarding coherence, discursive organization, lexical richness, and argumentation. Furthermore, the role of AI in formative feedback, idea generation, paraphrasing, and fostering student autonomy in self-editing their texts is highlighted. The research also identifies key challenges, such as students’ overreliance on AI, diminished metacognitive engagement, and ethical dilemmas related to plagiarism and authorship.DiscussionThe emergence of AI in higher education is transforming teaching and learning processes, creating opportunities for personalization and enhanced support in academic writing. However, the scientific literature also exposes tensions between its potential benefits and associated risks, such as student dependency, loss of critical thinking, and ethical concerns regarding authorship and plagiarism. These findings call for a rethinking of pedagogical, assessment, and institutional practices, as well as the development of critical and digital literacy skills among both teachers and students.